2021
DOI: 10.1177/11786302211017687
|View full text |Cite
|
Sign up to set email alerts
|

Protected but not from Contamination: Antimicrobial Resistance Profiles of Bacteria from Birds in a Ghanaian Forest Protected Area

Abstract: Resistance to antimicrobial agents is a growing concern in public health. It has been reported in wildlife from several places in the world though wild animals are not normally exposed to clinically used antimicrobial agents. Despite this, very little research has been done in Ghana to determine antimicrobial resistance in wild animals, particularly those in protected areas. In this study, the presence of colistin resistant and multidrug resistant (MDR) gram-negative bacteria in cloacal swabs of wild birds cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…(36% of the samples) from watering sites of migratory birds in Pakistan, which is higher than the present study. However, a lower detection rate (4.1%) was also recorded in Ghana by Modupe et al [30]. Moreover, Zhao et al [31] reported Shigella spp.…”
Section: Discussionmentioning
confidence: 86%
“…(36% of the samples) from watering sites of migratory birds in Pakistan, which is higher than the present study. However, a lower detection rate (4.1%) was also recorded in Ghana by Modupe et al [30]. Moreover, Zhao et al [31] reported Shigella spp.…”
Section: Discussionmentioning
confidence: 86%
“…Insects, birds, and animals that feed on agricultural plants and seeds can further disseminate resistant bacteria and genes. Furthermore, migratory birds have been shown to spread multiple antibiotic-resistant pathogens in various studies, highlighting the widespread nature of this problem [ 140 , 141 , 142 ]. Antibiotic-resistant pathogens have also been reported in chickens, further exacerbating the issue [ 113 ].…”
Section: Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…Moreover, a recent study reported the presence of antibiotic resistance in plant-growth-promoting bacteria [ 143 ]. Therefore, urgent action is needed to address this growing problem and ensure the continued effectiveness of antimicrobial therapies [ 113 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ].…”
Section: Mechanisms Of Antibiotic Resistancementioning
confidence: 99%
“…Modupe al. [62] isolated 10 bacteria genera including Shigella spp., Yersinia spp., Salmonella spp., Citrobacter spp., Enterobacter spp., Klebsiella spp., Proteus spp., Pseudomonas spp., Serratia spp., and Escherichia spp. from birds in a protected forest in Ghana.…”
Section: Diversity Prevalence and Zoonotic Risk Potential Ofmentioning
confidence: 99%